2003
DOI: 10.1074/jbc.m210909200
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonitis and Emphysema in sp-C Gene Targeted Mice

Abstract: SP-C-deficient (SP-C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
162
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 202 publications
(179 citation statements)
references
References 32 publications
13
162
2
2
Order By: Relevance
“…17,30 -36 SFTPCϪ/Ϫ mice bred into a congenic 129/SV background develop progressive pulmonary disease with parenchymal remodeling, airspace enlargement, and altered pulmonary mechanics. 30 In contrast, SP-C-deficient mice used in our studies (outbred Black Swiss background) show no evidence of lung inflammation or structural abnormalities. However, when combined with partial SP-B deficiency, SFTPCϪ/Ϫ mice (Black Swiss background) developed increased levels of interleukin-6 and interleukin-1␤ in bronchoalveolar lavage and a more severe impairment of pulmonary function than wild-type mice after exposure to hyperoxia.…”
Section: Discussioncontrasting
confidence: 40%
“…17,30 -36 SFTPCϪ/Ϫ mice bred into a congenic 129/SV background develop progressive pulmonary disease with parenchymal remodeling, airspace enlargement, and altered pulmonary mechanics. 30 In contrast, SP-C-deficient mice used in our studies (outbred Black Swiss background) show no evidence of lung inflammation or structural abnormalities. However, when combined with partial SP-B deficiency, SFTPCϪ/Ϫ mice (Black Swiss background) developed increased levels of interleukin-6 and interleukin-1␤ in bronchoalveolar lavage and a more severe impairment of pulmonary function than wild-type mice after exposure to hyperoxia.…”
Section: Discussioncontrasting
confidence: 40%
“…A complete pulmonary phenotype of this model has not been described. Any mistrafficking of proSP-C due to Nedd4-2 deficiency resulting in selective SP-C deficiency may not be phenotypically dominant as the SP-C null mouse survives to adulthood (45,46) due to redundancy in the biophysical activity provided by surfactant protein B. However, a preliminary report of a second independent Nedd4-2-deficient mouse indicated that perinatal lethality secondary to respiratory insufficiency can occur (47).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 90% of surfactant consists of saturated phospholipids, of which phosphatidylcholine is by far the most abundant component with some triacylglycerols and cholesterol, and 10% of lung-specific surfactant proteins (SPs), SP-A, SP-B, SP-C and SP-D 10 . Surfactant deficiency or disruption of production of SPs results in alveolar damage 11,12 . A variety of mutations in the SP-C gene have been identified in patients with pulmonary fibrosis 13,14 .…”
mentioning
confidence: 99%